Clinical considerations in the management of obesity in children and adolescents - Whitney Herring; Carina Kugelmas; Evan P. Nadler; Marsha Novick; Melissa Santos; Rachana Shah; Gitanjali Srivastava; Stephanie Walsh (Obesity Pillars)
Background: Obesity is a complex, chronic disease affecting more than one-fifth of adolescent children aged 12–19 years in the United States. Recent guidelines have recommended optimization of diagnosis and treatment approaches to help improve the immediate and long-term health of people with obesity. Methods: Here, we describe the insights and recommendations of 9 nationally recognized experts in pediatric obesity, summarized from a virtual advisory board discussion. Results: Advisors described their background, experiences, and patient populations, conveyed the journey experienced by many pediatric patients with obesity, discussed the recent landscape for pharmacotherapy in adolescents, and provided their perspectives on updated American Academy of Pediatrics Clinical Practice Guidelines. Conclusion: Overall, the advisors agreed that the key to addressing the growing prevalence of obesity in children and adolescents depends on increased education in the medical field and community-wide initiatives to promote early intervention. Collaboration among all parties (e.g., physicians, policymakers, insurance companies, academic institutions, and researchers) to address barriers to treatment and reduce the social stigma surrounding obesity is also essential.